Cardiac rehabilitation goal attainment after myocardial infarction with versus without diabetes: A nationwide registry study. (1st October 2019) - Wallert, John; Mitchell, Adam; Held, Claes; Hagström, Emil; Leosdottir, Margret; Olsson, Erik M.G.
Abstract: Background: Patients with first-time myocardial infarction (MI) and diabetes mellitus (DM) constitute a vulnerable subgroup of cardiovascular (CV) patients for which secondary prevention is particularly important. We investigated if patients with versus without DM differ in attaining four main lifestyle-related cardiac rehabilitation (CR) targets, one-year post-MI. Methods: This national cohort study (2006–2015) identified individuals with and without DM at hospital admission in the Swedish cardiac registry, SWEDEHEART. CR goal attainment was assessed one year later. The study population included 47, 907 unique patients with first-time MI <75 years at baseline (61.8 mean age, 26.7% women, 14.6% with DM). After imputation, propensity score matching was performed. Analyses were conducted with logistic regression. Results: In the matched population, having DM was associated (OR [95% CI]) with lower odds of attaining the one-year post-MI CR goal for both smoking cessation (0.90 [0.81, 0.99]) and attendance in exercise training (0.88 [0.83, 0.95]), yet with higher odds of the <1.8 mmol LDL-C target (1.28 [1.19, 1.36]), and similar odds for the <140 mm Hg systolic blood pressure target (0.97 [0.91, 1.04]). In addition, women with DM were particularly unlikely to attend exercise training. Conclusions: Patients with first-time MI and DM are less likely to attain two of four selected CR goals compared to those without DM. The particularly low exercise training attendance by women with DM is of concern. Possibilities for tailored interventions targeting behavioural change for this high-risk group, including focused efforts to increase exercise training attendance in women with DM, should be investigated. Highlights: Study of rehabilitation goal attainment post myocardial infarction with and without diabetes Patients with infarction and diabetes had lower odds of smoking cessation and attending exercise training. Women with diabetes were particularly unlikely to attend exercise training post infarction. Targeted care focused on behavioural change may benefit risk reduction in these patients. Intensified efforts to recruit women with diabetes into exercise training seem justified.